Visual Evaluation for Seed Yield in Pearl Millet - Yadav, O P; Manga, V K (Annals of Arid Zone, 2016)
The effectiveness of visual discrimination for seed yield was studied in pearl millet (Penuisetum glaucum). Results indicated that it is possible to visually discriminate the lines for seed yield in case the differences among them were large but not when such differences were small. Plots intermediate in yield were more prone to misjudgment during visual evaluation in comparison to high or low-yielding ones. The observer's perception of yield was influenced by plant height and earliness resulting into overestimation of actual yield for certain plots and underestimation for others. In general, correctly classified lines were taller, while no particular trend was observed with respect to earliness.